The Assyrian Stylized Tree: A Date Palm Plantation and Aššurnaṣirpal II’s Stemma - Franklin, Norma (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2022)
Aššurnaṣirpal II (r. 883–859 b.c.e.) moved his capital from Aššur to the old, long-deserted city of Kalḫu, which he proceeded to rebuild. His new official residence, the Northwest Palace, he described as his “palace for eternity.” The rooms of the palace had carved stone relief slabs, previously unknown in Assyria. Ten of the, known, rooms had depictions of stylized trees, as well as other figures. This chapter identifies the stylized trees as female date palms and their offshoots—clones of the original tree—together offering a stylized view of a date palm plantation. By exploring the scientific and linguistic data of date palms and the artistic and historical aspects of the reliefs, it appears that Aššurnaṣirpal used this stylized depiction of a date palm plantation as his stemma, an analogy of his unchanging hereditary right to rule.